2006
DOI: 10.1038/sj.npp.1301181
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone and Paliperidone Inhibit P-Glycoprotein Activity In Vitro

Abstract: Risperidone (RSP) and its major active metabolite, 9-hydroxy-risperidone (paliperidone, PALI), are substrates of the drug transporter P-glycoprotein (P-gp). The goal of this study was to examine the in vitro effects of RSP and PALI on P-gp-mediated transport. The intracellular accumulation of rhodamine123 (Rh123) and doxorubicin (DOX) were examined in LLC-PK1/MDR1 cells to evaluate P-gp inhibition by RSP and PALI. Both compounds significantly increased the intracellular accumulation of Rh123 and DOX in a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 40 publications
2
54
0
Order By: Relevance
“…3,11,12) This is the first report for a minimal role of P-gp in disposition of bupropion and its three major metabolites. Our results are in good agreement with our previous pharmacokinetic study in CF1 mice, in which risperidone, a substrate and inhibitor of P-gp 22,24,27) showed negligible effects on plasma and brain concentrations of bupropion and its metabolite HB. 22) The minimal involvement of P-gp in disposition of bupropion suggests that alteration of P-gp activity is not an important source for drug-drug interactions and variable therapeutic response of bupropion.…”
Section: Discussionsupporting
confidence: 92%
“…3,11,12) This is the first report for a minimal role of P-gp in disposition of bupropion and its three major metabolites. Our results are in good agreement with our previous pharmacokinetic study in CF1 mice, in which risperidone, a substrate and inhibitor of P-gp 22,24,27) showed negligible effects on plasma and brain concentrations of bupropion and its metabolite HB. 22) The minimal involvement of P-gp in disposition of bupropion suggests that alteration of P-gp activity is not an important source for drug-drug interactions and variable therapeutic response of bupropion.…”
Section: Discussionsupporting
confidence: 92%
“…Both drugs are substrates for P-glycoprotein, a transporter that limits brain penetration of a variety or drugs. Risperidone inhibits P-glycoprotein transport, whereas paliperidone is much less potent (Zhu et al, 2007), suggesting risperidone treatment could inhibit P-glycoprotein, allowing higher brain levels of paliperidone than would otherwise be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The entry of these drugs into CNS is significantly limited by P-glycoprotein. Furthermore, some of psychotropic agents were also found to be potent P-glycoprotein inhibitors and may influence the disposition of coadministered drugs which are likewise substrates of P-glycoprotein (Wang et al, 2006;Zhu et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%